Effects of Wavenumber and Chirality on the Axial Compressive Behavior of Wavy Carbon Nanotubes: A Molecular Mechanics Study. (13th October 2014) - Kawachi, Masaki; Kinoshita, Yusuke; Ohno, Nobutada
Abstract : The effects of wavenumber and chirality on the axial compressive behavior and properties of wavy carbon nanotubes (CNTs) with multiple Stone-Wales defects are investigated using molecular mechanics simulations with the adaptive intermolecular reactive empirical bond-order potential. The wavy CNTs are assumed to be point-symmetric with respect to their axial centers. It is found that the wavy CNT models, respectively, exhibit a buckling point and long wavelength buckling mode regardless of the wavenumbers and chiralities examined. It is also found that the wavy CNTs have nearly the same buckling stresses as their pristine straight counterparts.